2019
DOI: 10.1093/ageing/afy182
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity in middle and old age and risk of death from dementia: 40-year follow-up of 19,000 men in the Whitehall study

Abstract: Aims and objectives To examine the hypothesis that obesity is protective for dementia, we compared the associations of death from dementia with body weight and body mass index (BMI) in both middle and old age. Design: Height and weight were measured in a prospective study of 19,019 middle aged men in the Whitehall study in 1967-1970 and in 6158 surviving participants at resurvey in 1997. Cox regression was used to examine the associations of death from dementia over a 40-year period with weight or BMI measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Our findings of the association between weight loss and dementia are generally consistent with the results from previous studies, [6][7][8][9][10][11][12][13]28 but most of them were conducted among Caucasians who usually had larger body weight and weight change than Asians. The Whitehall study suggested that a ≤-7.5 kg weight loss over 30 years from midlife to late-life was associated with risk of death from dementia compared to stable weight (-2.5 -+2.5 kg).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of the association between weight loss and dementia are generally consistent with the results from previous studies, [6][7][8][9][10][11][12][13]28 but most of them were conducted among Caucasians who usually had larger body weight and weight change than Asians. The Whitehall study suggested that a ≤-7.5 kg weight loss over 30 years from midlife to late-life was associated with risk of death from dementia compared to stable weight (-2.5 -+2.5 kg).…”
Section: Discussionsupporting
confidence: 91%
“…4 There has been accumulating evidence that weight loss during adulthood is associated with dementia. [5][6][7][8][9][10][11][12][13] However, most studies were conducted among Caucasians 7-13 that usually have higher body weight and weight change than Asians. One study suggested that a weight loss of ≤-7.5kg over 30 years was significantly associated with risk of death from dementia, 7 whereas others reported a > 5% loss in body mass index (BMI) over 3 to 9 years was associated with dementia risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the role of individual nativity and neighborhood-level nativity (immigrant concentration) on weight, BMI, and WC over time in a cohort of older Latinos. We found that, among older Latinos, weight and BMI decreased over time; this has been documented in other aging populations (Allen et al, 2019;Karahalios, English, & Simpson, 2016). Foreign born Latinos had lower baseline weight and BMI than US-born Latinos, even with adjustment for age, gender, and height.…”
Section: Discussionsupporting
confidence: 70%
“…In aging populations, change in obesity and weight are complex factors; although obesity can be a risk factor for other diseases/outcomes, weight and body composition (i.e., fat distribution, muscle mass, and height) are often found to decrease with increasing age (Allen, Clarke, Shipley, & Leon, 2019;Cetin & Nasr, 2014;Miller & Wolfe, 2008;Rothman, 2008). A large number of studies in older populations have reported that weight loss is associated with increased risk of death (Park et al, 2018).…”
mentioning
confidence: 99%